2005
DOI: 10.1159/000088348
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Growth after Withdrawal of Exogenous Glucocorticoids

Abstract: Background: The growth-suppressive effect of systemic glucocorticoids in children is well established, however, recovery of growth after withdrawal of short-term treatment in school-age children has not been evaluated. Objective: To assess short-term growth after withdrawal of systemic glucocorticoids. Methods: A post-hoc analysis of data from a double-blind lower leg growth trial which compared 5 mg prednisolone once daily in the evening with placebo was performed. The study consisted of run-in, treatment, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…As recommended all children were included in the study within few weeks and the duration of the study was less than 3 months to avoid possible confounding seasonal variations in growth rate (14). The finding of no carryover effects and similar treatment‐free growth rates confirmed that 2 weeks wash out periods were sufficient, thus, supporting recent evaluations of the duration of short‐term growth suppressive effects of exogenous glucocorticoids (15). The mean values of and ranges of growth rates were comparable with observations in healthy children, in asthmatic children and in children with allergic rhinitis (5,6,16).…”
Section: Discussionsupporting
confidence: 84%
“…As recommended all children were included in the study within few weeks and the duration of the study was less than 3 months to avoid possible confounding seasonal variations in growth rate (14). The finding of no carryover effects and similar treatment‐free growth rates confirmed that 2 weeks wash out periods were sufficient, thus, supporting recent evaluations of the duration of short‐term growth suppressive effects of exogenous glucocorticoids (15). The mean values of and ranges of growth rates were comparable with observations in healthy children, in asthmatic children and in children with allergic rhinitis (5,6,16).…”
Section: Discussionsupporting
confidence: 84%
“…A review of the literature, however, reveals that the action of systemic glucocorticosteroids depends on both the dosage and the duration of the treatment. The use of these drugs causes a rise in exogenic cortisol, which interferes with lipid metabolism by increasing the uptake of lipids in the digestive system and by promoting storage of lipids in the tissues, especially in the shoulders and trunk, while usually leaving the extremities lean [38].…”
Section: Discussionmentioning
confidence: 99%
“…A great majority of the children in both parallel groups were treated with inhaled budesonide during the year prior to enrolment in the study and a treatment free run in of only 1 wk was applied. A recent analysis of the duration of short-term growth suppression after withdrawal of exogenous corticosteroids found good evidence that a 1 wk wash out allows for full recovery of suppressed short-term lower leg growth rates (20). It may be questioned, however, whether catch-up in height growth to some extent may have affected the results in the montelukast treated group.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 52 pre-pubertal children with asthma were included in a randomized open-label parallel group study. Length of the lower leg and height were measured by knemometry and stadiometry, respectively, at study entry and after 2,4,12,20,28,36,44 and 52 wks. Lower leg and height growth rates were significantly lower in the budesonide than in the montelukast group (p < 0.0001).…”
mentioning
confidence: 99%